13C MRS and LC–MS Flux Analysis of Tumor Intermediary Metabolism - Shestov, Alexander A.; Lee, Seung-Cheol; Nath, Kavindra; Guo, Lili; Nelson, David S.; Roman, Jeffrey C.; Leeper, Dennis B.; Wasik, Mariusz A.; Blair, Ian A.; Glickson, Jerry D. (Frontiers in Oncology, 2016)
We present the first validated metabolic network model for analysis of flux through key pathways of tumor intermediary metabolism including glycolysis, the oxidative and non-oxidative arms of the pen-tose pyrophosphate shunt, the TCA cycle as well as its anaplerotic pathways, pyruvate malate shut-tling, glutaminolysis and fatty acid biosynthesis and oxidation. The model that is called Bonded Cumomer Analysis for application to 13C MRS data and Fragmented Cumomer Analysis for mass spectrometric data is a refined and efficient form of isotopomer analysis that can readily be expanded to incorporate glycogen, phospholipid and other pathways thereby encompassing all the key pathways of tumor intermediary metabolism. Validation was achieved by demonstrating agreement of experi-mental measurements of the metabolic rates of oxygen consumption (MRO2), glucose consumption, lactate production and glutamate pool size with independent measurements of these parameters in cultured human DB-1 melanoma cells. These cumomer models have been applied to studies of DB-1 melanoma and DLCL2 human diffuse large B-cell lymphoma cells in culture and as xenografts in nude mice at 9.4 T. The latter studies demonstrate the potential translation of these methods to in situ studies of human tumor metabolism by MRS with stable 13C isotopically labeled substrates on instru-ments operating at high magnetic fields (≥7 T). The melanoma studies indicate that this tumor line obtains 51% of its ATP by mitochondrial metabolism and 49% by glycolytic metabolism under both euglycemic (5 mM glucose) and hyperglycemic conditions (26 mM glucose). While a high level of glutamine uptake is detected corresponding to ~50% of TCA cycle flux under hyperglycemic condi-tions, and ~100% of TCA cycle flux under euglycemic conditions, glutaminolysis flux and its contri-butions to ATP synthesis were very small. Studies of human lymphoma cells demonstrated that inhi-bition of mTOR signaling produced changes in flux through the glycolytic, pentose shunt and TCA cycle pathways that were evident within 8 hours of treatment and increased at 24 and 48 hours. Lac-tic acid was demonstrated to be a suitable biomarker of mTOR inhibition that could readily be moni-tored by 1H MRS and perhaps also by FDG-PET and hyperpolarized 13C MRS methods.